Rooting of Passiflora actinia Hook stem cuttings: IBA concentrations and application forms - Tomazzoli, Maíra Maciel; Fagundes, Cintia de Moraes; Amatussi, Juliana de Oliveira; Breiter, Bruna Santos Klein; Zuffellato-Ribas, Katia Christina (Revista de Ciências Agroveterinárias, 2019)
The Caatinga passion fruit (Passiflora actinia Hook) is used as rootstock for different passion fruit species due to its tolerance to low temperatures. This study aimed to evaluate the efficiency of the stem cutting technique in the vegetative propagation of P. actinia according to different concentrations of indole butyric acid (IBA) and application methods. The experiment was conducted in the greenhouse of Federal University of Parana, between August and October 2016. Semi-woody stem cuttings measuring 10 cm long were treated with 0, 1500, and 3000 mg Kg-1/mg L-1 IBA in talc and solution, and then planted in plastic tubes with vermiculite as substrate. After 60 days, the stem cuttings were evaluated for rooting percentage, presence of callus, survival, new shoots, number of roots per cuttings and average length of the longest root. The best rooting percentage (85.94%) and number of roots/cuttings were found in cuttings treated with IBA in talc at 3.000 mg Kg-1 and 1.500 mg Kg-1, respectively. P. actinia propagation by stem cuttings is an efficient method. IBA, in both application forms, efficiently promoted the rooting of the species and can be recommended at the concentration of 1.500 mg Kg-1 or mg L-1.